Role of Gab1 in Heart, Placenta, and Skin Development and Growth Factor- and Cytokine-Induced Extracellular Signal-Regulated Kinase Mitogen-Activated Protein Kinase Activation - Itoh, Motoyuki (American Society for Microbiology, 2000)
Gab1 is a member of the Gab/DOS (Daughter of Sevenless) family of adapter molecules, which contain a pleckstrin homology (PH) domain and potential binding sites for SH2 and SH3 domains. Gab1 is tyrosine phosphorylated upon stimulation of various cytokines, growth factors, and antigen receptors in cell lines and interacts with signaling molecules, such as SHP-2 and phosphatidylinositol 3-kinase, although its biological roles have not yet been established. To reveal the functions of Gab1 in vivo, we generated mice lacking Gab1 by gene targeting. Gab1-deficient embryos died in utero and displayed developmental defects in the heart, placenta, and skin, which were similar to phenotypes observed in mice lacking signals of the hepatocyte growth factor/scatter factor, platelet-derived growth factor, and epidermal growth factor pathways. Consistent with these observations, extracellular signal-regulated kinase mitogen-activated protein (ERK MAP) kinases were activated at much lower levels in cells from Gab1-deficient embryos in response to these growth factors or to stimulation of the cytokine receptor gp130. These results indicate that Gab1 is a common player in a broad range of growth factor and cytokine signaling pathways linking ERK MAP kinase activation.